Influence of La2O3 addition on activity and coke formation over Ni/SiO2 for acetic acid steam reforming. (19th January 2022) - Guo, Wenwen; Li, Guoneng; Zheng, Youqu; Li, Ke; Guo, Long
Abstract: The influence of the addition amount of lanthanum oxide on the activity and coke formation over Ni/SiO2 catalyst for hydrogen production from AcOH steam reforming was studied in the paper. Through the catalyst characterization and experimental research, it was found that with the addition of La2 O3 the particle size of the active metal Ni decreased, and the active Ni-support interaction was enhanced. With the optimal addition amount of La2 O3 (30 wt %), Ni/30LaSi catalyst displayed the highest activity with the high carbon conversion rate of 98.8%. The surface morphology and thermogravimetric analysis of the spent catalyst revealed that the carbon deposition was mainly in the form of filamentous coke and the diameter of the carbon fiber was related with the Ni particle size. The addition of suitable La2 O3 can inhibit the formation of carbon deposition, decrease the content of encapsulating coke, and improve the catalyst stability. Highlights: The optimal addition amount of La2 O3 (30 wt%) was obtained for Ni/SiO2 . The carbon deposition was mainly in the form of filamentous carbon. La2 O3 addition promoted catalyst activity and inhibited coke formation. La2 O3 promoter enhanced Ni dispersion and reduced Ni particle size.